Book review: Anita R. Fedor (2021): Regional characteristics of the precariat on the labour market. Debrecen University Press, Debrecen - Markovics, Márton; Varga, Zsombor; Tóth, Dalma (Acta Medicinae et Sociologica, 2023)
-